(1650) Using Intelligent Decision Support Systems in Selected Aspects of Health Care استخدام أنظمة دعم القرار الذكية في جوانب مختارة من الرعاية الصحية - El Haddad, Basmah (معهد التخطيط القومى, 2022)
The research introduces the need of using agent technologies in assisting and aiding the responsible parties and decision markers during the decision-making process in general and in the human organ transplantation management.